Managing Social Resilience on Outermost Small Islands Through Cross-Border Cooperation: A Study of The Marore Islands, Indonesia - Sandy Nur Ikfal Raharjo; Bayu Setiawan; Esty Ekawati; M. Fakhry Ghafur (Jurnal Archipelago, 2024)
Small island communities have become one of the most vulnerable groups to climate risks and natural disasters, including in the Marore Islands located on the border between Indonesia and Philippines. The people of Marore face vulnerabilities such as geographic isolation, extreme weather, limited infrastructure and transportation, low levels of education and healthcare, and high poverty rates. This research aims to analyze the role of cross-border cooperation between Indonesia and Philippines in enhancing the social resilience of the Marore Islands community. Through a qualitative approach, data was collected through interviews, focused discussions, and observations. This study found that the implementation of cross-border cooperation in the form of the Border Crossing Agreement (BCA) and Border Trade Agreement (BTA) positively contributes to the improvement of four out of six dimensions of social resilience, namely human, financial, social, and political. However, this role is still hindered by the unequal political will of both governments, institutional weaknesses in the implementing agencies, and the outdated provisions of agreements made in the 1950s-1970s. Therefore, the BCA and BTA need to be reevaluated, especially regarding the objectives of cross-border activities, the geographic scope, the threshold value for customs duties, and the types of traded commodities.